Reflections on the Popular in the Context of the Grupo Mamulengo de Cheiroso de Teatro de Bonecos - Rodrigues, Pedro (Revista Brasileira de Estudos da Presença, 2023)
This article presents and discusses the notion of popular culture and theater based on the experience of the Grupo Mamulengo de Cheiroso de Teatro de Bonecos (Aracaju/SE), a popular nucleus with a specific relationship with the academic space. The study is a partial result of a master’s research and makes extensive use of literature review, primary sources, and interviews. Through these discussions, a critical view of popular theater is obtained, which can manifest itself in different places, modes, and contexts, deviating from a stereotyped and largely homogeneous view of these phenomena, resulting from literary production that approaches history from the perspective of lettered culture.